Analysis of Container Yard Requirements at Sorong Container Port - Idris, Muhammad; Siswanto, Siswanto (Institut Teknologi Sepuluh Nopember, 2024)
Along with the increase in trade activities by sea, the need for adequate port facilities, including the Container Yard, is becoming increasingly important. This study aims to analyze the needs of stacking yard facilities at Sorong Container Port. The research method used is a quantitative approach with data collection through documentation studies and observation at the research location, namely Sorong Container Port. The results showed that although the flow of containers is projected to continue to increase until 2026, the use of the stacking yard is still low with a Yard Occupancy Ratio (YOR) ranging from 12.43% to 14.59%. This indicates an opportunity to improve port operational efficiency. This study recommends optimizing the use of the piling yard, improving the loading and unloading process, developing infrastructure, and improving coordination with stakeholders. Further analysis of infrastructure investment and comparative studies with other ports are also recommended.